Continuous renal replacement therapy during extracorporeal membrane oxygenation: why, when and how?. Issue 6 (December 2018) - Ostermann, Marlies; Connor, Michael; Kashani, Kianoush
Abstract : Purpose of review: The use of extracorporeal membrane oxygenation (ECMO) is increasing rapidly. Patients on ECMO have a high risk of developing acute kidney injury (AKI) and needing renal replacement therapy (RRT). The aim of this review is to describe different strategies of combining RRT and ECMO and to outline their advantages and drawbacks. Recent findings: Fluid overload is the most common indication for RRT during ECMO, and continuous renal replacement therapy (CRRT) is the most commonly used modality. The optimal timing for initiation of CRRT should be individualized based on degree of fluid overload and severity of AKI-related metabolic derangements. In ECMO patients, CRRT can be provided via an integrated approach (i.e. in-line haemofilter or a fully integrated CRRT device) or a parallel system with separate ECMO and RRT circuits. In-depth knowledge of the resulting intra-circuit pressure changes, risks of air entrapment and haemolysis, and implications for ultrafiltration and solute clearance are essential. There is no evidence that the different methods of combining ECMO and CRRT impact mortality. Summary: In patients on ECMO, CRRT can be provided via an integrated approach or independently via parallel systems. An in-depth understanding of the advantages and drawbacks of the different techniques is required.